Study on the dynamic relationship among economic policy uncertainty, bitcoin and energy price - Wu, Renhong; Xie, Yiming; Jahan, Nusrat; Fang, Yuantao (Asian Journal of Economic Modelling, 2025)
Bitcoin has garnered significant interest among investors, policymakers, practitioners, and market participants, with factors such as the Russia-Ukraine war and the constantly changing global uncertainties making crude oil prices unstable. The purpose of this paper is to examine the dynamic impact of Economic Policy Uncertainty (EPU) on the linkage between Bitcoin and crude oil prices using the TVP-VAR method, which represents a major starting point of this study. Through model analysis, it was found that, first, in the study examination, the linkage between EPU and the Bitcoin market is relatively high, implying the possibility of diversified relations. Second, the relationship between EPU and crude oil prices is quite significant in the short run, and the results also show that EPU’s impact on crude oil prices is much more stable than on Bitcoin, a crucial factor to consider when assessing the impact of uncertainty on the interaction between Bitcoin and crude oil price markets. Third, there is evidence that Bitcoin’s hedging properties for crude oil prices throughout the sample period are undeniable, having significant policy implications for policymakers and market participants. Therefore, in studying economic variables, EPU is an important influencing factor that policymakers and investors need to consider.